Evaluation of Kinnow Mandarin Fruit Waste in Rations of Goats - Kour, Ravleen; Rastogi, Ankur; Sharma, R.K.; Singh, Manmeet (Indian Journal of Animal Nutrition, 2018)
A study was conducted to evaluate the effect of kinnow mandarin (Citrus nobilis Lour x Citrus deliciosa Tenora) waste (KMW) inclusion in the ration on feed intake and nutrient utilization in goats. Twelvelocal adult male goats (age= 8-10 months; BW= 23.00 kg) were randomly allotted to two equal groups designated as control and treatment. All the animals were fed wheat straw ad lib. supplemented with either conventional concentrate mixture (control) or 40% KMW containing concentrate mixture (Treatment). Body weights of the animals and nutrient digestibility was not affected due to treatments. KMW inclusion widened the Ca: P ratio due to high content of Ca in KMW suggesting that maintaining Ca: P ratio needs carefulconsideration while feeding KMW in ration. There was no adverse effect of KMW inclusion in dietary ration on the general health of the goats as indicated by blood biochemical parameters.